Upaya Guru PAI dalam Mengembangkan Karakter Disiplin melalui Pembiasaan Shalat Dhuha di MAN 2 Payakumbuh - Siti Mesaroh; Fauzan Fauzan; Wedra Aprison; Alimir Alimir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research was motivated by field observations at MAN 2 Payakumbuh City in October 2021, which found that most students did not perform dhuha prayer. The reasons found include lack of facilities such as clean mukena, laziness, and lack of understanding of the virtues of dhuha prayer. This habit shows the low awareness of students of the importance of familiarizing dhuha prayer as part of daily life. This study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research informants consisted of MAN 2 Payakumbuh students as key informants, and PAI teachers as supporting informants. The results showed that PAI teachers' efforts in developing students' disciplinary character through habituation of dhuha prayers included the application of punishments such as ruku for several minutes and additional assignments, such as memorizing verses of the Qur'an. In addition, teachers provide motivation, advice, and good examples. Support from the school, teachers, and student guardians is a supporting factor for the success of this program. However, there are obstacles such as differences in student characters, lack of collaboration between teachers, and lack of parental support. One of the main obstacles is the lack of understanding provided by other teachers about the importance of dhuha prayer, which results in low participation.